Multilevel analysis of factors associated with pregnancy termination in Ethiopia. (August 2022) - Yemane, Getahun Dejene; Korsa, Birhanu Bedada; Jemal, Sebwedin Surur
Abstract: Background: Pregnancy termination is a major public health issue that affects maternal mortality around the world. So the study aimed to identify factors that are associated with pregnancy termination in Ethiopia. Methods: Community-based crossectional data came from Ethiopia's Mini Demographic and Health Survey 2019. The current study's sample included women who had their pregnancy terminated (aged 15–49) and had complete information on all factors of interest (N = 8885). The binary logistic regression model investigated the factors that contribute to pregnancy termination in Ethiopia and multilevel logistic regression were used to identify regional variation in Ethiopia. Results: The current study showed that the prevalence of pregnancy termination in Ethiopia was 8.6%. The likelihood of pregnancy termination in uneducated women was 1.5 times (AOR = 1.479, 95% CI = 1.205–1.816) lower than in women who attended elementary school, 1.5 (AOR = 1.476, 95% CI = 1.107–1.969) lower than Secondary attended women and 1.8 times (AOR = 1.755, 95% CI = 1.270–2.427) lower than Higher school attended women. The likelihood of pregnancy termination in rural women was 0.8 times (AOR = 0.753, 95% CI = 0.573–0.990) higher than in urban women. Conclusion: The current study showed that there was regional Variation among women in Ethiopia to terminate the pregnancy. The characteristics of education level, place of residency, marital status and contraceptive knowledge are significant and differ between regions of the country. As a result, increasing contraception use and enhancing women's knowledge are the most effective ways to avert the problem. Highlights: Pregnancy termination is a major public health issue that affects maternal mortality around the world. The study aimed to identify factors that are associated with pregnancy termination in Ethiopia. Community-based crossectional data came from Ethiopia's Mini Demographic and Health Survey 2019. The current study showed that the prevalence of pregnancy termination in Ethiopia was 8.6%. The current study showed that there was regional Variation among women in Ethiopia to terminate the pregnancy. As a result, increasing contraception use and enhancing women's knowledge are the most effective ways to avert the problem.